2011
DOI: 10.1088/1748-6041/6/2/021001
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior of tetragonal zirconia polycrystal versus titanium and titanium alloy

Abstract: The aim of this study was to clarify the influence of tetragonal zirconia polycrystal (TZP) on the two-body wear behavior of titanium (Ti). Two-body wear tests were performed using TZP, two grades of cp-Ti or Ti alloy in distilled water, and the cross-sectional area of worn surfaces was measured to evaluate the wear behavior. In addition, the surface hardness and coefficient of friction were determined and an electron probe microanalysis performed to investigate the underlying mechanism of wear. The hardness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…NA implants are made of cold worked cp-titanium resulting in an enhanced Vickers hardness (unpublished data). Increasing the hardness of a metal is usually accompanied with an increased yield strength and therefore the material exhibits a higher threshold for the occurrence of plastic deformation [40,42]. All implants show chipping and plastic deformation, suggesting forces exceeding the elastic properties of the material [40].…”
Section: Discussionmentioning
confidence: 99%
“…NA implants are made of cold worked cp-titanium resulting in an enhanced Vickers hardness (unpublished data). Increasing the hardness of a metal is usually accompanied with an increased yield strength and therefore the material exhibits a higher threshold for the occurrence of plastic deformation [40,42]. All implants show chipping and plastic deformation, suggesting forces exceeding the elastic properties of the material [40].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the t-test showed a significant difference before and after tests in the groups fastened with grade 4 pure titanium screws, with ZrB-Ti4S showing the highest loosening torque ratio. In terms of the Vickers hardness of the materials used in this study, it is reportedly 177 Hv for grade 4 pure titanium, 256 Hv for Ti-6Al-4V, and 1356 Hv for Y-TZP 5) , and these were the combinations used in the study that showed the greatest difference in hardness between materials. Therefore, cyclic loading tests were also performed at the centric point.…”
Section: Loosening Torque Ratio After Cyclic Loading Test (Ltr2)mentioning
confidence: 81%
“…When a screw is tightened, a frictional force occurs at the contact surface of the screw, and shear stress due to the torsional torque and axial stress caused by the axial force are applied to the screw 29) . Kanbara et al 5) reported that in wear tests on pure titanium and Ti-6Al-4V, abrasive wear was caused by Y-TZP. Therefore, abutment screws for zirconia implants should be fabricated out of zirconia.…”
Section: Abutment Screws Used For Zirconia Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an in vitro study on wear between titanium alloy and zirconia20 has reported that the amount of wear of titanium alloy opposing zirconia was 20 times higher than that of the zirconia, and pointed out that this is due to the hardness of zirconia. In addition, a previous study20 has also described that, while adhesive wear occurred between metal and metal, abrasive wear occurred between zirconia and metal. In the present case, a secondary electron image revealed the presence of Ni-Cr alloy as a foreign body on the zirconia surface (Fig.…”
Section: Discussionmentioning
confidence: 99%